On Some Examples of Williamson Matrices - Manjhi, Pankaj Kumar; Kujur, Ninian Nauneet (Communications in Mathematics and Applications, 2023)
This article deals with some special cases of Williamson Hadamard matrices, which are generated by block symmetric circulant matrices. In these cases, the patterns of the obtained examples have been analyzed for insight into the nature of the Williamson matrices.